EFL Students’ Experiences and Attitudes Toward Situated e-Portfolio English Writing - Wu, Chia Pei (JET (Journal of English Teaching), 2023)
Electronic portfolios make new possibilities of making students to write differently in the new era. In this study, 36 Tourism and Hospitality major students participated in Situated e-Portfolio English writings in a Practical English class using Wix.com. This study aimed to investigate students' experiences and attitudes toward this e-Portfolio writing in a situated learning context. Research question one asked how Taiwanese EFL students perceive the e-Portfolio writing activity. Research question two asked about students' attitudes toward their e-Portfolio. Questionnaires and reflection entries were utilized for data collection. The result shows positive experiences and attitudes. The results show that EFL Taiwanese Students positively affect English e-Portfolio writing and enthusiastic attitudes.